Myval Beyond the Aortic Valve: Device–Anatomy Interaction, Procedural Strategy, and Clinical Evidence in Mitral, Tricuspid, and Pulmonary Positions - Georgios E. Papadopoulos; Ilias Ninios; Sotirios Evangelou; Apostolia Marvaki; Maria Kalaitzoglou; Andreas Ioannides; Grigorios Giamouzis; Vlasis Ninios (Bioengineering, 2026)
The Myval balloon-expandable transcatheter heart valve was developed for transcatheter aortic valve implantation, but its broad 20–32 mm size matrix and controlled deployment have prompted use in non-aortic landing zones. This narrative review critically synthesizes Myval-specific case reports, case series, and observational cohorts, together with relevant platform-level evidence, addressing device design, anatomical selection, imaging, procedural strategy, clinical outcomes, and evidence gaps. Reported applications include mitral valve-in-valve, valve-in-ring, and valve-in-mitral annular calcification; tricuspid valve-in-valve and valve-in-ring; and pulmonary implantation in conduits, surgical bioprostheses, and selected native or patched right ventricular outflow tracts. Outcomes appear most predictable within circular stented surgical bioprostheses, whereas non-circular rings, severe mitral annular calcification, and compliant or aneurysmal outflow tracts present greater risks of inadequate anchoring, paravalvular regurgitation, embolization, frame deformation, left ventricular outflow tract obstruction, and coronary compression. Intermediate and extra-large diameters increase the available nominal sizing options; however, no clinical evidence demonstrates that this reduces embolization, paravalvular regurgitation, residual gradients, or reintervention. The available data document procedural feasibility in anatomically selected patients but are predominantly observational, with limited independent adjudication and follow-up. These procedures are generally off-label and should remain individualized Heart Team decisions; prospective multicenter studies are required to define comparative safety, antithrombotic management, durability, and lifetime reintervention strategies.